Wychowanie religijne dzieci i młodzieży szkolnej na ziemiach polskich przełomu XIX i XX wieku w świetle literatury pięknej i pamiętnikarskiej - Galek, Czesław (Studia Pastoralne, 2009)
The research objective of the article is to show the methods and forms of religious education of school children and students in the late 19th and early 20th centuries in the territory of Poland based on fiction and memoir writings. Religious instruction teachers were responsible for teaching religion at schools. Some of them conducted classes in accordance with the teaching methodology; they were able to make students interested in religious matters, and they were treated as authorities and became their students’ spiritual mentors. Others did not contribute much to the religious and moral shaping of young people, due to the lack of teaching skills or appropriate knowledge, or because they treated their duties carelessly. The authorities representing foreign rule in the territory of Poland, by treating religion instrumentally, forced students to various religious practices, which created a negative effect, and turned the students off religion and the Church. Many students were deep believers and practicing Catholics. However, lack of proper educational impact caused some students’ difficulties with faith. Some of them even considered themselves atheists. The source material presented in the article can also be instructive for contemporary teachers of religious education.